النمذجة الحاسوبية ودراسة الحالة العابرة لنقل الموائع في الأنابيب الطويلة - النجار, رائد; حمودة, محمد (Latakia University Journal -Engineering Sciences Series, 2017)
تعتبر نمذجة الحالة العابرة في الأنظمة الهيدروليكية ذات الأنابيب الطويلة من أصعب وأهم الحالات بحثاً. ولتحقيق الدراسة يستخدم نموذج المقاومة المتغيرة لوصف تدفق السائل المتغير في الأنبوب. حيث يوصف من خلال معرفة طبيعة إجهاد القص بجدار الأنبوب وأيضاً معرفة طبيعة الجريان (صفحي أم مضطرب).إن نتائج محاكاة الصدمة الهيدروليكية التي يسببها الانتقال المفاجىء لصمام التحكم الهيدروليكي درست في الحالات التالية :1- تحسين معدل تصريف ثابت للمضخة.2- تحسين معدل تصريف متغير للمضخة.وأخيراً مقارنة نتائج المحاكاة الحاسوبية مع النتائج التجريبية.It is a cross in the hydraulic systems with long pipes case modeling of the hardest and most important cases in search. Of the most important and is considered Query to achieve study the changing resistance model is used to describe the changing liquid flow in the tube.As described by knowing the nature of the shear stress to the pipe wall and also know the nature of the flow ( laminar or turbulent ).The results of simulations of hydraulice shock caused by the sadden move of the hydraulic control valve which studied in the following cases:1- Hard to improve the discharge of the pump rate.2- Improve the discharge of the pump variable rate finally; compare the results of computer simulations with experimental results.